The Rietveld Method applied to quantitative phase analysis of minerals containing disordered structures - Bonetto, Rita Dominga (2003)
The Rietveld method was successfully used for the quantitative phase analysis (QPA) of zeolitized rocks containing montmorillonite, a phase in which the atomic positions cannot be determined exactly. The freely distributed program FULLPROF was used in its profile-matching mode with CuKα X-ray data. This program permit carrying out quantitative analysis without using structural data for one of the phases. This method was applied to a set of reference mixtures of kaolinite and quartz, in order to show its effectiveness compared to normal refinement. The composition of these synthetic mixtures covered the range between 10 wt% and 90 wt% of both components. The absolute errors were lower than 5 wt%. Also, a set of artificial mixtures of quartz, clinoptilolite, and montmorillonite were quantified with the profilematching mode applied to montmorillonite. The absolute errors were lower than 6 wt%. Ten different measurements and refinements were carried out on one of these samples to obtain estimates of the true standard deviations of the concentrations. The average error values obtained are similar to the error reported by the FULLPROF program from a single refinement. The application of the method to two zeolitized tuffs of the Chubut Group, Patagonia, Argentina, with different percentages of clinoptilolite, quartz, feldspars, and clay minerals resulted in an absolute error of 3 wt% (compared to the results estimated by chemical and thermogravimetric analysis). For the zeolite phase (clinoptilolite), it was necessary to refine the occupation parameters of the exchangeable cations and the structural water molecules. The results indicate that quantitative analysis by the Rietveld method, using the FULLPROF program in the profilematching mode for one of the phases, may be used as a routine tool for the characterization of mineral samples that contain phases with disordered structures.